Preparation and Characterization of Magnetic Solid Lipid Nanoparticles as a Targeted Drug Delivery System for Doxorubicin - Abbas Soltani; Parvaneh Pakravan (Tabriz University of Medical Sciences, 2023)
Purpose: In the present study, we investigated the magnetic solid lipid nanoparticles (mSLNs) for targeted delivery of doxorubicin (DOX) into breast cancer cells. Methods: The synthesis of iron oxide nanoparticles was carried out by co-precipitation of a ferrous and ferric aqueous solution with the addition of a base; moreover, during precipitation process, the magnetite nanoparticles should be coated with stearic acid (SA) and tripalmitin (TPG). An emulsification dispersion-ultrasonic method was employed to prepare DOX loaded mSLNs. Fourier transforms infrared spectroscopy, vibrating sample magnetometer, and photon correlation spectroscopy (PCS) were used to characterize the subsequently prepared nanoparticles. In addition, the antitumor efficacy of particles was evaluated on MCF-7 cancer cell lines. Results: The findings showed that entrapment efficiency values for solid lipid and magnetic SLNs were 87±4.5% and 53.7±3.5%, respectively. PCS investigations showed that particle size increased with magnetic loading in the prepared NPs. In vitro drug release of DOX-loaded SLN and DOX-loaded mSLN in phosphate buffer saline (pH=7.4) showed that the amount of drug released approached 60% and 80%, respectively after 96 h of incubation. The electrostatic interactions between magnetite and drug had little effect on the release characteristics of the drug. The higher toxicity of DOX as nanoparticles compared to free drug was inferred from in vitro cytotoxicity. Conclusion: DOX encapsulated magnetic SLNs can act as a suitable and promising candidate for controlled and targeted therapy for cancer.